Jus post bellum: Justice at the End of War: The Interrelationship Between the Three Conditions of JW To Post War Justice (Journal of Advanced Research in Social Sciences, 2021)
Post bellum justice considers vindication of human rights and prosecution on occasion of its violation essential to establish just peace at the end of war. An inquiry into the interrelationship between justice in the commencement, during, and at the end of war reveals the centrality of human rights and just peace. Conversely, jus post bellum's failure is associated with discrepancies in jus ad bellum and jus in bello conditions of just war (JW). The study, therefore, observes an intricate relationship between the three conditions of just war. This correlation is further stressed on the importance of jus ad bellum criteria of right intention and proportionality principle of jus in bello to rightly administer judgment for crimes committed during war. To complement the already existing laws of warfare, the paper distinguished crimes based on intention into presumptuous, not-presumptuous, and un-presumptuous. Thus, all three conditions of just war synergistically work together to justify a just war claim for right resort to force.